Microstructural Stability and Creep Behavior of a Re/Ru Single-Crystal Nickel-Based Alloy - Ning Tian (Crystals)
By testing the creep properties of a Re/Ru-containing single-crystal alloy specimen and examining the microstructural evolution of the allow at different stages of creep using scanning electron microscopy (SEM) and transmission electron microscopy (TEM), the deformation and damage mechanisms of the alloy under ultra-high temperature conditions were investigated. It was observed that a dislocation network forms before the rafting of the γ′ phase. As creep progresses, this network becomes increasingly dense and complete. Moreover, the dislocation network undergoes a transformation from the <110>-type to the <100>-type configuration, with a hybrid <110>-<100>-type network representing an intermediate state during the transition. Stacking faults were also identified within the γ′ phase, suggesting that the stacking fault energy of this alloy is lower compared to that of other alloys. During creep, dislocations that penetrate the γ′ phase can undergo cross slip from the {111} plane to the {100} plane under applied stress, resulting in the formation of Kear–Wilsdorf (K–W) immobile dislocation locks. These locks hinder further dislocation movement within the γ′ phase. It is concluded that the damage mechanism of the alloy at the later stage of creep under 120 MPa/1160 °C involves initial crack formation at the interface of the twisted raft-like γ/γ′ two-phase structure. As creep continues, the crack propagates in a direction perpendicular to the applied stress axis.